2021
DOI: 10.1097/j.pain.0000000000002427
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting neuropathic from poststroke pain: the white matter within

Abstract: Poststroke pain (PSP) is a heterogeneous term encompassing both central neuropathic (ie, central poststroke pain [CPSP]) and nonneuropathic poststroke pain (CNNP) syndromes. Central poststroke pain is classically related to damage in the lateral brainstem, posterior thalamus, and parietoinsular areas, whereas the role of white matter connecting these structures is frequently ignored. In addition, the relationship between stroke topography and CNNP is not completely understood. In this study, we address these i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 87 publications
(126 reference statements)
0
11
0
Order By: Relevance
“…A very recent study confirmed that damage of the white matter surrounding the posterior insular point plays a crucial role in the occurrence of poststroke central pain. 13 These authors interpreted their findings in the framework of the EPIC model. 3 According to this model, the anterior insula (and possibly other agranular cortical regions within the so-called pain matrix) continuously sends predictions to the granular cortex of the PIMO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A very recent study confirmed that damage of the white matter surrounding the posterior insular point plays a crucial role in the occurrence of poststroke central pain. 13 These authors interpreted their findings in the framework of the EPIC model. 3 According to this model, the anterior insula (and possibly other agranular cortical regions within the so-called pain matrix) continuously sends predictions to the granular cortex of the PIMO.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of the white matter underlying this area could provide a means to disentangle the different contributions. Prediction and prediction-error neurons, believed to project to the anterior insula 13 and located in the most superficial white matter layer of the U fibers, should be less activated than thalamic inputs when stimulating the white matter in the depth of the cortex. In this article, we report, for the first time, the results of electrical white matter stimulation in a series of patients operated on for a glial tumor in the PIMO region.…”
Section: Introductionmentioning
confidence: 99%
“…In these cases, the pain is chronic and debilitating, with all characteristics of central pain caused by a spinothalamic tract deafferentation. A very recent study con rmed that damage of the white matter surrounding the posterior insular point plays a crucial role in the occurrence of central pain 39 . In the present series, none of the patients experienced chronic central pain.…”
Section: Surgical Interestmentioning
confidence: 98%
“…3 Although focus is generally put on spinal, brainstem, thalamic, or parietoinsular lesions, the role of the thalamocortical white matter is commonly ignored. 5 Reports of lesions involving specifically white matter paths connecting the thalamus with the PIMO rarely address the development of central pain (see one exception in Ref. 1).…”
mentioning
confidence: 99%
“…However, a recent study in 89 patients who had a stroke with or without central poststroke pain (CPSP) showed that interruption of thalamo-PIMO white matter connections was a critical determinant of central pain, which could identify patients with CPSP and differentiate this group not only from strokes without pain but also from patients with pain of nonneuropathic origin. 5 Modern techniques of tractography such as those used in the study by Mandonnet et al should allow for early selection of patients at risk to develop central pain after brain lesions and therefore optimize pre-emptive or therapeutic interventions.…”
mentioning
confidence: 99%